ANALISIS PENGARUH HALAL TOURISM TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA: STRATEGI DAN TANTANGAN - Felia Maghfira; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
Halal Tourism is one of the most promising economic sectors in the world, including Indonesia. As a source of income or foreign exchange for the country, Halal Tourism should pay attention to its development. The purpose of this study is to analyze the extent of the influence of Halal Tourism on economic growth in Indonesia and the strategies that are deployed to face the existing challenges. The method used in this study is a qualitative method with literature study analysis. The results of this study indicate that the Indonesian population is dominated by Muslims, which allows Indonesia to develop Halal Tourism even more actively. Indonesia has been selected as the